Evolutionary Thinking in Environmental Economics - Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2007)
Evolutionary and environmental economics have a potentially close relationship. This paper reviews past and identifies potential applications of evolutionary concepts and methods to environmental economics. This covers a number of themes: resource use and ecosystem management; growth and environmental resources; economic and evolutionary progress; and individual behavior and environmental policy. The treatment will address both biological and economic—including institutional, organizational and technological-evolutionary phenomena. Attention will be drawn to the fact that evolutionary economics shows a surprising neglect of environmental and natural resource factors.
Keywords: B52; O3; O4; Q2; Q5; 330; Coevolution; economic growth; environmental policy; innovation; progress; self-regulation; renewable resources; resilience; social preferences; Wirtschaftswachstum; Technischer Fortschritt; Umwelt; Erneuerbare Ressourcen; Soziale Wohlfahrtsfunktion; Evolutionsökonomik; Umweltökonomik